THE ROLE AND STRATEGIC SIGNIFICANCE OF HUMAN CAPITAL IN THE ECONOMIC DEVELOPMENT OF UZBEKISTAN (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the importance of human capital in the economic development of Uzbekistan and the necessity of modernizing the higher education system. In the context of globalization, the rise of the digital economy, and increasing competition in the international labor market, investments directed toward the educational sector are interpreted as one of the key strategic priorities of the state. The article substantiates the invaluable role of human capital in developing a highly qualified workforce, strengthening scientific potential, and facilitating the transition to an innovation-driven economy. Additionally, the paper highlights the role of education in Uzbekistan’s socio-economic development strategies, existing challenges, and solutions for their effective elimination.